Application of geometric dimensioning and tolerancing to connector design - Soh, Lip Teck. (2008)
Even though Geometric Dimensioning and Tolerancing (GDT) is a good drawing specification tool, widely accepted and used in most industries, there are needs to improve on its usage. This dissertation explores the important reasons behind GDT usage, specifically to the connector industry. It explains the needs to gather information from connector application, processing, manufacturing and inspection, in order to have an overall view of the requirements needed, before applying GDT to connector design. Obstacles, limitations and difficulties on GDT usage are discussed, so as to raise the awareness of their existence. Some of the common mistakes and improper application of GDT are covered as well. It is hope that these topics will be able to address some of the needs of the connector industry in area of GDT application.